2009
DOI: 10.1073/pnas.0813112106
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing Z + agrin splicing in Nova null mice restores synapse formation and unmasks a physiologic defect in motor neuron firing

Abstract: Synapse formation at the neuromuscular junction (NMJ) requires an alternatively spliced variant of agrin (Z ؉ agrin) that is produced only by neurons. Here, we show that Nova1 and Nova2, neuronspecific splicing factors identified as targets in autoimmune motor disease, are essential regulators of Z ؉ agrin. Nova1/Nova2 double knockout mice are paralyzed and fail to cluster AChRs at the NMJ, and breeding them with transgenic mice constitutively expressing Z ؉ agrin in motor neurons rescued AChR clustering. Surp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
113
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 48 publications
3
113
1
Order By: Relevance
“…SMN functions in snRNP biogenesis as part of the SMN-Gemins complex (16,20) and SMN deficiency causes tissue-specific snRNA repertoire perturbations (15,26), which likely elicit the mRNA expression and splicing abnormalities found in MNs and WM at this early presymptomatic stage. We have not detected changes in mRNAs encoding neuronspecific splicing factors, such as Nova1/2, which can regulate agrin's Z exon splicing (56), or neural polypyrimidine tract-binding proteins (57) at P1. However, abnormalities detected in several other transcription and splicing factors (e.g., Etv1, Fos, Trp53, Tra2b and Celf3) (Datasets S2-S4) could potentially explain why the transcriptome defects in SMA exacerbate over time (15,28).…”
Section: Discussionmentioning
confidence: 99%
“…SMN functions in snRNP biogenesis as part of the SMN-Gemins complex (16,20) and SMN deficiency causes tissue-specific snRNA repertoire perturbations (15,26), which likely elicit the mRNA expression and splicing abnormalities found in MNs and WM at this early presymptomatic stage. We have not detected changes in mRNAs encoding neuronspecific splicing factors, such as Nova1/2, which can regulate agrin's Z exon splicing (56), or neural polypyrimidine tract-binding proteins (57) at P1. However, abnormalities detected in several other transcription and splicing factors (e.g., Etv1, Fos, Trp53, Tra2b and Celf3) (Datasets S2-S4) could potentially explain why the transcriptome defects in SMA exacerbate over time (15,28).…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches can be used to interrogate isoforms in AS regulatory networks, and recent examples emerging from genetic analysis of Nova-regulated AS events illustrate their power. For example, phenotypic analyses of Nova knockout mice have revealed defects in neuromuscular junction (NMJ) morphology and impaired neuronal migration during development (Ruggiu et al 2009;Yano et al 2010). The aforementioned approaches used to identify Nova-regulated isoforms identified target exons in agrin and disabled-1 transcripts, which are genes with known roles in NMJ formation and neuronal migration, respectively.…”
Section: Determining the Role Of Tissue-specific Isoformsmentioning
confidence: 99%
“…These studies demonstrate that the complexity involved in the formation of this simple, large peripheral synapse is only beginning to be unravelled. For example, the NMJ defects in Nova1 and Nova2 mutant mice cannot be rescued by overexpressing neuronal agrin in motoneurons (Ruggiu et al, 2009), suggesting the existence of additional neuronal factors.Mutations in and/or autoimmune reactions to some proteins essential for NMJ development cause muscular dystrophies, including myasthenia gravis and congenital myasthenic syndrome (reviewed by Engel et al, 2008). Studies of NMJ formation could identify potential culprits and therapeutic targets for these disorders.…”
mentioning
confidence: 99%
“…Direct interactions between nerve terminals and muscle fibers might be mediated by adhesion molecules, including neural cell adhesion molecule [NCAM (Polo-Parada et al, 2004)], CD24 [a glycosylphosphatidylinositol (GPI)-linked protein (Jevsek et al, 2006)], the immunoglobin proteins Syg1 and Syg2 (Shen and Bargmann, 2003;Shen et al, 2004), and embigin (Lain et al, 2009). However, the mechanisms by which NMJ development is regulated by cell adhesion remain to be elucidated.Finally, recent studies have identified several genes the mutation of which leads to NMJ development defects, including the neuronspecific splicing factors Nova1 and Nova2 (Ruggiu et al, 2009), amyloid precursor protein (APP) , dystrophinassociated proteins (Adams et al, 2004; Banks et al, 2009;Grady et al, 2000;Grady et al, 2003), the glycosyltransferase Large , the protein degradation components Fbxo45, Nedd4, Usp14 and Uchl1 (Chen et al, 2009;Chen et al, 2010;Liu et al, 2009;Saiga et al, 2009), the chromatin organization protein HP1 (Aucott et al, 2008) and meltrin b, a metalloprotease (Yumoto et al, 2008). These studies demonstrate that the complexity involved in the formation of this simple, large peripheral synapse is only beginning to be unravelled.…”
mentioning
confidence: 99%